ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS GIZI BALITA SUKU ANAK DALAM (SAD) (Studi di Wilayah Kerja Puskesmas Pematang Kabau Kecamatan Air Hitam Kabupaten Sarolangun Jambi) - Fitri, Reza Kartika; Pradigdo, Siti Fatimah; Rahfiludin, Muhammad Zen (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Malnutrition is the most important problem because of the direct impact to growth retardation. Inadequate nutritional intake in toddler particularly in 24-59 months will lead to growth retardation. The aim of this research was to analyze factors affecting toddler’s nutritional status in inner child’s tribe in Pematang Kabau Health Center, Sarolangun Regency, Jambi. This was a quantitative research with cross sectional design. Population of this research were mothers of inner child’s tribe in Pematang Kabau Health Center, Sarolangun Regency in total of 40 people. Sampling technic of this research was using purposive sampling of the total population. Data was analyzed using Rank Spearman. Results of this research showed that most of the toddler’s nutritional status was Good (70%). Mother’s knowledge was classified as good (57,5%), toddlers who were taboo of eggs and livestock were 37,5%. Most toddlers had a big family (92,5%). Most toddlers had adequate energy intake (72,5%) and adequate protein intake (65%). Toddlers who had infectional disease were 60%. There were a significant correlation between toddler’s nutritional status in inner child’s tribe with food taboo (p=0,001), energy intake (p=0,001), protein intake (p=0,001) and infectional disease (p=0,007). Otherwise, mother’s knowledge and number of family members had no significant correlation with toddler’s nutritional status in inner child’s tribe. It is necessery for the health center to monitor toddler’s nutritional status periodically. Especially for inner child’s tribe whose nutritional status is good to keep maintaining them. Mothers could be involved in Integrated Service Posts as Cadres so they could share their knowledge to other mothers.